2012
DOI: 10.1038/tp.2012.119
|View full text |Cite
|
Sign up to set email alerts
|

Integrated copy number and gene expression analysis detects a CREB1 association with Alzheimer’s disease

Abstract: Genetic variation, both single-nucleotide variations and copy number variations (CNV), contribute to changes in gene expression. In some cases these variations are meaningfully correlated with disease states. We hypothesized that in a genetically heterogeneous disorder such as sporadic Alzheimer's disease (AD), utilizing gene expression as a quantitative trait and CNVs as a genetic marker map within the same individuals in the context of case–control status may increase the power to detect relevant loci. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…A previous study demonstrated that subjects with spatial memory impairment had lower hippocampal levels of CREB1 (Brightwell et al, 2004 ). CREB is a member of the family of leucine-zipper transcription factors, while CREB1 has been reported to promote cell signal transduction (Li et al, 2012 ). What’s more, the phosphorylation of CREB1 has been highlighted due to its involvement in the synthesis of an array of proteins, of which play significant roles in neuronal functions, including that of protein kinase A (PKA) (Murphy Jr et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that subjects with spatial memory impairment had lower hippocampal levels of CREB1 (Brightwell et al, 2004 ). CREB is a member of the family of leucine-zipper transcription factors, while CREB1 has been reported to promote cell signal transduction (Li et al, 2012 ). What’s more, the phosphorylation of CREB1 has been highlighted due to its involvement in the synthesis of an array of proteins, of which play significant roles in neuronal functions, including that of protein kinase A (PKA) (Murphy Jr et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Predicting the development and prognosis of AD is difficult, however, because only a small percentage of cases present with an autosomal dominant transmission pattern and an early disease onset that make genetic testing practical. To date, three causal genes have been identified which together account for less than 2% of AD: amyloid-beta protein precursor (APP) gene on chromosome 21 (Goate et al, 1991), presenilin1 (PSEN1) gene on chromosome 14 (Sherrington et al, 1995), and presenilin 2 (PSEN2) gene on chromosome 1 (Levy-Lahad et al, 1995; Sherrington et al, 1995) (Li et al, 2012). It has been suggested that a DNA diagnosis is attainable in about 70% of families with autosomal dominant AD and a clinical approach to genetic testing is well described (Liddell et al, 2001).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…LINC00550 is of unknown function; however, it is overexpressed in neurofibrillary tangles as compared to neurons in subjects with AD (GEO: GDS2795). The chr2: 208,35 deletion upstream from CREB1 has been reported previously from the same dataset using alternative statistical approach incorporating gene expression as a quantitative trait and CNV into the model [24]. The chr15: 30,44 region was reported to be associated with AD [23].…”
Section: Discussionmentioning
confidence: 88%